Two-pion Bose-Einstein correlations in central Pb-Pb collisions at √sNN=2.76 TeV - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Lohner, Daniel; Lu, Xianguo; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; et al. (Physics letters, 2011)
The first measurement of two-pion Bose-Einstein correlations in central Pb-Pb collisions at sNN=2.76 TeV at the Large Hadron Collider is presented. We observe a growing trend with energy now not only for the longitudinal and the outward but also for the sideward pion source radius. The pion homogeneity volume and the decoupling time are significantly larger than those measured at RHIC.
Available online 30 December 2010
*ALICE Collaboration: K. Aamodt, V. Anguelov, O. Busch, P. Glässel, R. Grajcarek, N. Herrmann, J. Klein, D. Lohner, X.G. Lu, J. Mercado Perez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, S. Vallero, B. Windelband [und 901 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 17.02.2022